A comparative evaluation of the antimicrobial effect of chamomile, Aloe vera-green tea, and chlorhexidine mouthwashes on some oral bacterial species - Narges Naghsh; Ahmad Moghareabed; Mahsa Nematnejad; Jaber Yaghini; Sayed Mohsen Sadeghi (Dental Research Journal, 2023)
Background: Plant compounds such as Aloe vera, green tea, and chamomile have been increasingly used in recent years to achieve oral health. This study aimed to determine the antimicrobial effect of chamomile (Matrika), A. vera-green tea, and chlorhexidine (CHX) mouthwashes on some oral bacterial species. Materials and Methods: This prospective experimental study investigated the antimicrobial properties of three mouthwashes, including chamomile (Matrika), A. vera -green tea, and CHX as well as distilled water as control on five bacterial species, including Streptococcus Oralis, Streptococcus sanguis, and Streptococcus mutans as primary colonizers and Porphyromonas gingivalis and Eikenella corrodens as secondary colonizers. Colony-forming unit was used to count the colonies and disc diffusion and well diffusion methods were used to measure the diameter of zone of inhibition. Data were analyzed by SPSS (version 22) software using descriptive statistics, ANOVA, Tukey, Kruskal–Wallis, and Mann–Whitney tests (α = 0.05). Results: CHX had a significantly higher antibacterial effect than the other two mouthwashes in all three methods (P < 0.001). Further, the herbal mouthwashes in all three methods had a statistically significant effect on the bacterial species (P < 0.001). A. vera-green tea mouthwash had a significantly higher effect than chamomile mouthwash (Matrika) on all bacterial species except for S. sanguis (P < 0.05). Conclusion: The findings showed that herbal mouthwashes had potentially antibacterial effects, but these effects were significantly lower than that of CHX. However, more clinical studies are needed to prove the current findings.